Factors influencing audit report lag in Malaysian public listed companies / Amanuddin Shamsuddin ... [et al.] - Shamsuddin, Amanuddin; Zahar, Amira Natasha; Mohd Zahar, Anis Amira; Rengasamy, Mithrah (UiTM Cawangan Johor, 2019)
Timeliness of audited financial statement is significantly influenced by the length of the audit process. The purposes of this study is to identify the level of audit report lag (ARL) in Malaysian public listed companies and to investigate the factors that influence ARL in Malaysia. This study extends the previous studies by using the sample of 725 public listed companies in Bursa Malaysia for the year 2017. Secondary data from the companies' annual reports were used in this study. The results show that 97.7% (708 out of 725) of public listed companies complied with Bursa Malaysia requirements to have audited financial statement prepared within 4 months; hence on 17 (2.3%) companies did not comply. Meanwhile, the average number of days taken by companies to issue their audited financial statement is between 95 to 96 days. The results also indicate that there is a significant relationship between audit tenure, audit firm reputation and ARL. However, there is no significant association between type of industry and ARL. Findings from this study would contribute to practitioners and relevant regulatory bodies such as Bursa Malaysia, Malaysian Institute of Accountants in ensuring that ARL can be reduced or minimised.